New Dizziness Impact Measures of Positional, Functional, and Emotional Status Were Supported for Reliability, Validity, and Efficiency - Daniel Deutscher, PT, MScPT, PhD; Deanna Hayes, PT, DPT, MS; Michael A. Kallen, PhD, MPH (Archives of Rehabilitation Research and Clinical Translation, 2024)
Objective: To calibrate the 25 items from the Dizziness Handicap Inventory (DHI) patient-reported outcome measure (PROM), using item response theory (IRT), into 1 or more item banks, and assess reliability, validity, and administration efficiency of scores derived from computerized adaptive test (CAT) or short form (SF) administration modes. Design: Retrospective cohort study. Setting: Outpatient rehabilitation clinics. Participants: Patients (N=28,815; women=69%; mean age [SD]=60 [18]) included in a large national dataset and assessed for dizziness-related conditions who responded to all DHI items at intake. Interventions: Not applicable. Main Outcome Measures: IRT model assumptions of unidimensionality, local item independence, item fit, and presence of differential item functioning (DIF) were evaluated. Generated scores were assessed for reliability, validity, and administration efficiency. Results: Patients were treated in 976 clinics from 49 US states for either vestibular-, brain injury-, or neck-related impairments. Three unidimensional item banks were calibrated, creating 3 distinct PROMs for Dizziness Functional Status (DFS, 13 items), Dizziness Positional Status (DPS, 4 items), and Dizziness Emotional Status (DES, 6 items). Two items did not fit into any domain. A DFS-CAT and a DFS 7-item SF were developed. Except for 2 items by age groups and 1 item by main impairment, no items were flagged for DIF; DIF impact was negligible. Median reliability estimates were 0.91, 0.72, and 0.79 for the DFS, DPS, and DES, respectively. Scores discriminated between patient groups in clinically logical ways and had a large effect size (>0.8), with acceptable floor and ceiling effects (<15%), except for a floor effect for DPS (20.4%). DFS-CAT scores were generated using a median of 8 items; they correlated highly with full-bank scores (r=0.99). Conclusion: The 3 dizziness impact PROMs demonstrated moderate to high reliability, were valid, and highly responsive to change; thus, they are suitable for research and routine clinical administration.